ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI UBI KAYU DI KECAMATAN TERBANGGI BESAR KABUPATEN LAMPUNG TENGAH - Sony Putra; Rabiatul Adawiyah; Achdiansyah Soelaiman (Lampung University, 2021)
The objectives of this research were to find out the income of cassava farming and the contribution to household income, and household welfare level of cassava farmers. The location was determined purposively, considering that Terbanggi Besar Sub-District has been the center of cassava production in Central Lampung Regency. The number of respondents was 66 respondents and taken randomly. Data were collected in July 2019. The analytical method used farm analysis and BPS welfare indicators (2014). This research showed that average income of cassava farmimg was IDR685,276.62 per month and the contribution of cassava farming income to household income was 36.9%. Based on BPS indicators, cassava farmer households in Terbanggi Besar Sub-District were mostly categorized as not prosperous farmer families. Key words: cassava farmers, household income, welfare level.